IR and the Global South: Revising Obstacles to a Global Discipline - Oztig, Lacin Idil (Institute of International Studies, 2023)
The IR discipline is marked by a strong center-periphery inequality that is perpetuated through theories, methodologies, and concepts produced in the Global North that do not adequately capture the diverse experiences of Global South states and societies. In tandem with growing critiques of Western-centrism and calls for global IR, the discipline has now become more heterogeneous and inclusive, and IR scholars are more attentive to the global IR debate than ever before. Yet, the discipline has not become truly global, as many Global South scholars are absent from the major debates in the field and there are still sharp geographic differences with respect to IR knowledge production. Even though Global South countries have enormous potential to enrich and globalize IR with their history, political thinkers, and religious and philosophical traditions, this potential remains largely untapped. While Global South scholars develop alternative perspectives and engage in theorizing practices, these efforts have not yet been embodied in the form of an IR theory that provides alternative explanations of world politics. Equally important, these perspectives are not echoed in much of the mainstream accounts in IR. This study contributes to the global IR debate by problematizing the dynamics behind the insufficient development and representation of Global South IR theories and perspectives in the discipline. After delving into entrenched Western-centrism and the asymmetries of knowledge production in the discipline, the present study puts into spotlight the intellectual and material barriers that feed off each other and perpetuate the inequalities in IR knowledge production.